A recepção crítica da obra de Dalcídio Jurandir : Rio de Janeiro e Belém do Pará (1940 – 1980) - Barbosa, Wilson Ferreira (2016)
Dalcídio Jurandir Ramos Pereira was born in Vila de Ponta de Pedras, Ilha de Marajó, in the state of Pará, Brazil, on 10 January 1909. He is a great exponent of Brazilian Literature since 1941, when his first novel, Chove nos campos de Cachoeira, was published by Editora Vecchi in Rio de Janeiro. His work has great value as a registration of Pará‟s culture. In that sense, the aim of this thesis is to do a literature review of his work, especially around what he wrote for newspapers and magazines of Rio de Janeiro and Belém (Pará‟s capital), the two cities in which he was most active. The newspapers due to be examined are those that were in circulation between 1940 and 1980, a phase that corresponds to the divulgation of his work. All the original documentation is archived in the “Fundação Casa Rui Barbosa”, in Rio de Janeiro, and the first editions (the originals) of each novel were found in a store held by the writer‟s family in the “Casa de Culture Dalcídio Jurandir”, located in Niterói, state of Rio de Janeiro. The thesis, which can be put in the field of Literary Criticism and History of Literature, is not just about analyzing the referred material but also gathering and transcribing the essays about the writer, presenting them in the appendix for researchers interested in his work to consult. Dalcídio Jurandir published eleven novels between 1941 and 1978. Ten of them became known as novels of the “Ciclo do Extremo Norte”, a name given by the writer himself, who also said they reveal “life in Pará in terms of fiction.” In 1959, Dalcídio published Linha do parque, a novel that narrates the working class‟s struggles in Rio Grande do Sul; this novel was translated to Russian in 1962. Dalcídio Jurandir got many awards with these novels: in 1960 he won the Paula Brito award, from the Biblioteca do Estado da Guanabara and, in that same year, the Luiza Cláudio de Souza award. In 1972 won the Machado de Assis award, granted by the Academia Brasileira de Letras, for lifetime achievement.